Capitalization of Tourism Development Policy in Lombok West Nusa Tenggara Indonesia - Winengan, Winengan (Jurnal Ilmiah Peuradeun, 2019)
This study aims to examine the interests of the actors involved in the policy formulation of land acquisition for the development of Mandalika Resort area in Lombok that caused community opposition reaction, as it will remove them from the land they have occupied for years as their residence and earn a living as farmers. This research used qualitative method of critical paradigm, by determining the informant in snow ball sampling technique. Data collection was done by interview and documentation techniques. Data analysis referred to an interactive model. While the data validity test used data credibility criteria. The results of this research states that the tourism policy by the local government actors and tourism development companies to facilitate business interests or policy capitalization has caused the value in the importance of local communities which has never been taken into account in the determination of local-level policies.